POTENSI Trichoderma viride DALAM MENEKAN SERANGAN Sclerotium rolfsii PADA TANAMAN KEDELAI (Glycine max L.) - Si H Wahyuni (Jurnal Agrotek Lestari, 2018)
Potential  of Trichoderma viride to control Sclerotium rolfsii on soybean (Glycine max L.). This research aims to determine the  potential of T. viride against S. rolfsii attack on soybean crop (Glycine max L.). The research was conducted in the field of Faculty of Agriculture, Graha Nusantara University Padangsidimpuan, from May to August 2017. The results showed the highest percentage disease of incidence of S. rolfsii at the highest observation of 2, 3, 4 MST (Week After Planting), from W2D0 (when planting / 75 gram /polybag) 46.77%, 61.35% and 73.29%. and the lowest was W1D4 (7 days before planting/300 gram / polybag) 1.8%, 2.3% and 3.41%. Keywords : Potential, Trichoderma viride, Sclerotium rolfsii, Soybean